A new species of spider mite, Oligonychus neocastaneae sp. nov. (Acari: Tetranychidae), from Japan - Arabuli, Tea; Gotoh, Tetsuo (Zootaxa, 2018)
A new species Oligonychus neocastaneae sp. nov. is described and illustrated from Castanea crenata Sieb. et Zucc. (Fagaceae). The new species closely resembles Oligonychus castaneae Ehara & Gotoh, 2007, which inhabits the same host plant, Castanea crenata, but mainly differs by the aedeagus in having a longer distal portion which forms a small sigmoid and acuminate tip, instead of having a shorter distal portion which ends in a truncate tip. Several differences were also observed between the two species in the leg setal counts of tarsus II in the male and female; the number of tactile setae and solenidia (in parentheses) was 11(1) for the female and male in the new species, but in O. castaneae this count is 12(1) for the female and 12(2) for the male. A maximum likelihood tree based on the cytochrome c oxidase subunit I (COI) gene of mitochondrial DNA (mtDNA) showed that O. neocastaneae sp. nov. was clearly separated from O. castaneae and other related species. A key to all species of the genus Oligonychus known in Japan is given.